The sensitivity of film-forming strains of staphylococci, isolated from the respiratory tract, to bacteriophages drugs - O. S. Voronkova; O. A. Sirokvasha; T. M. Shevchenko; A. I. Vinnikov; V. YE. Kudryavtseva (Zaporožskij Medicinskij Žurnal)
Aim. To determine the sensitivity of filmforming strains of staphylococci, isolated from the respiratory tract, to bacteriophages drugs